Повышение качественных характеристик термоантрацита для производства угольной продукции металлургического назначения - Цыбуля, Е. И. (НТУ "ХПИ", 2014)
Рассмотрены показатели качества антрацита, применяемого для производства угольной продукции, и их изменение в зависимости от температуры прокаливания. Проведен статистический анализ формы кусков антрацита до и после прокаливания и рассчитана их удельная поверхность. Предложено для повышения качества угольной продукции металлургического назначения использовать термоантрацит высокотемпературного прокаливания.

Made an analysis of factors affecting on production characteristics carbon production of metallurgical destination. Shown significant influence on operational characteristics has been providing quality raw materials, used for production carbon products, main thing among of which stands anthracite (thermoanthracite). Considered indicators of anthracite quality, used for the production of metallurgical coal production, and change depending on the calcination temperature. Shown the most important quality indicator of thermoanthracite is specific electric resistance, which greatly depends on anthracite temperature in the furnace heating.
Improving thermoanthracite quality characteristic for production of metallurgical coal destination
Keywords: электродная масса; электрокальцинатор; прокаливание; температура; удельное электрическое сопротивление; anthracite; thermoanthracite; electrode mass; electrocalcinator; calcination; temperature; specific electric resistance